2010
DOI: 10.1007/s00277-009-0897-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological response to influenza vaccine after hematopoetic stem cell transplantation

Abstract: Vaccination is the best strategy to prevent influenza infection that is a potential cause of morbidity and mortality in immunosuppressed patients. Here, we evaluated the factors that may affect serological response to influenza vaccine in patients who have undergone hematopoetic stem cell transplantation (HSCT). Sixty-one HSCT recipients were included in the study during the 2007-2008 influenza season. Serum samples prior to vaccination and 6-10 weeks after vaccination were collected. Samples were assayed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The variable rate of seasonal trivalent influenza vaccination in our cohort (39% in 2009, 37.8% in 2008, 20.7% in 2007, and 13.4% in 2006) makes it difficult to discern the overall vaccine immune response to these antigens versus possible previous seasonal influenza infection. Overall, seroprotection against all of the influenza viruses observed was modest, even in patients who received the trivalent vaccine, with particularly low titers to influenza B, consistent with previous reports [16,17]. …”
Section: Discussionsupporting
confidence: 91%
“…The variable rate of seasonal trivalent influenza vaccination in our cohort (39% in 2009, 37.8% in 2008, 20.7% in 2007, and 13.4% in 2006) makes it difficult to discern the overall vaccine immune response to these antigens versus possible previous seasonal influenza infection. Overall, seroprotection against all of the influenza viruses observed was modest, even in patients who received the trivalent vaccine, with particularly low titers to influenza B, consistent with previous reports [16,17]. …”
Section: Discussionsupporting
confidence: 91%
“…1,2,6-8 Seroconversion rates after vaccination are slightly better when vaccination occurs earlier in the course of anticancer therapy. 9 There is also a varied response depending on the immunosuppressive extent of a patient's antineoplastic regimen, with particularly marked effects in patients undergoing SCT. 8,9 In transplant patients, a recent study in adults found no difference in increased T-cell-mediated immunity in patients given 1 versus 2 doses of the vaccine posttransplantation, arguing that attention to providing $1 dose of the immunization in patients with cancer can produce significant benefit.…”
mentioning
confidence: 99%
“…9 There is also a varied response depending on the immunosuppressive extent of a patient's antineoplastic regimen, with particularly marked effects in patients undergoing SCT. 8,9 In transplant patients, a recent study in adults found no difference in increased T-cell-mediated immunity in patients given 1 versus 2 doses of the vaccine posttransplantation, arguing that attention to providing $1 dose of the immunization in patients with cancer can produce significant benefit. 5 Conversely, 2 recent pediatric studies demonstrated better immunogenicity in children with cancer after repeated doses and with use of higher adult doses.…”
mentioning
confidence: 99%
“…Post-transplantation immunosuppression remains a major problem for the immunogenicity of the H1N1 vaccine [8,9]. None of the presented patients had been vaccinated.…”
Section: Discussionmentioning
confidence: 99%